A flexible photo-thermoelectric nanogenerator based on MoS2/PU photothermal layer for infrared light harvesting. (July 2018) - He, Minghui; Lin, Yu-Jhen; Chiu, Che-Min; Yang, Weifeng; Zhang, Binbin; Yun, Daqin; Xie, Yannan; Lin, Zong-Hong
Abstract: Recently, ambient energy harvesting has attracted a great deal of attention to develop clean and renewable energy technologies. In this work, a flexible photo-thermoelectric nanogenerator (PTENG) based on MoS2 /PU photothermal film and Te/PEDOT thermoelectric layer has been demonstrated for harvesting environmental infrared (IR) light. The MoS2 /PU photothermal film is carefully designed to exhibit excellent flexibility, transferability, and photothermal property. By integrating the photothermal layer with a Te/PEDOT thermoelectric device, the PTENG can produce electrical output without a spatial temperature gradient which is necessary for conventional thermoelectric device. Under IR light illumination, a high temperature difference can be generated across the device, and hence a potential difference established between two electrodes based on a coupling of photothermal effect and Seebeck effect. This type of PTENG exhibits numerous advantages, such as flexible, shape-adaptive, light-weight, and simple-fabrication, which may have a great potential of application in photo-thermoelectric energy harvesting for wearable electronics and implantable electronics. Graphical abstract: fx1 Highlights: A photo-thermoelectric nanogenerator based on MoS2/PU and Te/PEDOT has been demonstrated for harvesting infrared light. The PTENG can produce electrical output without a spatial temperature gradient needed for conventional thermoelectric device. This type of PTENG exhibits numerous advantages, such as flexible, shape-adaptive, light-weight, and simple-fabrication.